The Doctrine Of Illegality Under Section 24 Of The Malaysian Contracts Act, 1950: Laying A Spirit to Rest - Suhana, Sharifah (Journal of Malaysian and Comparative Law, 2019)
The case of Theresa Chong v Kin Khoon & Co is important to Malaysian contract law because to date, it is the only case which attempts an interpretation of section 24, in particular section 24(e) of the Malaysian Contracts Act 1950, regarding the scope of "public policy".